Assessing Combinatorial Design for Analyzing System Performance of a Computer Network - Ahmed, Bestoun S.; Mohammad, Amin S.; Essa, Hemin T. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Generally, combinatorial design concerns with the arrangement of finite set of elements into patterns (subsets, words, arrays) according to specified rules. The usefulness of this design method is that the number of input combination can be reduced dramatically but all of them are covered by the combinatorial set. This paper presents the application of this design method in communication networks. Communication engineers can use this novel method to generate test cases for producing cost-effective set of experiments to recognize the factors that have the least and most impact on the system's performance. A well-known scenario is used for the purpose of the experiment and five factors with different values are chosen to qualify their effect on the network performance. The experimental set is generated using combinatorial design method and then it is been used to analyze the effect of each factor. The experiments showed the effectiveness of the method to be used for analyzing the effect of factors on communication network. Keywords: Communication networks; combinatorial design; software testing; performance evaluation; network design; design of experiments
Keywords: Communication networks combinatorial design software testing performance evaluationnetwork design design of experiments